Effect of Waterlogging at Different Growth Stages on Growth, Yield and Biochemical Characteristics of Brinjal (Solanum melongena L.) - Choudhury, Shormin; Kayes, Amrul; Rahman, Naimur; Ahmmad, Sajib; Islam, Nazrul; Shawon, Tanzena Akter (European Journal of Applied Sciences, 2025)
Waterlogging affects a variety of plants, including brinjal; however, little is known about the consequences of waterlogging on brinjal at various growth stages. A pot experiment was carried out on two brinjal cultivars, BARI brinjal 8 and BARI brinjal 11, to study the effects of waterlogging at various growth stages on plant growth, chlorophyll content, malondialdehyde (MDA) content, reducing sugar, proline, phenol, and fruit yield. The experiment was carried out using waterlogging treatments applied at the four-five-leaf and flowering stages, with standard management (no waterlogging) as a control. The negative effects of waterlogging on brinjal growth varied with waterlogging timing, with the greatest influence occurring during the flowering stage, followed by the seedling stage. BARI brinjal 8 was more susceptible to waterlogging than BARI brinjal 11. Waterlogged conditions reduced the chlorophyll content, ultimately lowering grain yield. Biochemical parameters such as proline, reducing sugar, phenol, and MDA concentration, changed under waterlogging stress, with the change being more pronounced during the flowering stage. It was observed that, plants that received watering at the seedling stage recovered. However, during the flowering stage, waterlogging may cause morphological development to stall and hinder brinjal production from recovering.